1994
DOI: 10.1002/ajmg.1320530204
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype/Karyotype correlations of Y chromosome aneuploidy with emphasis on structural aberrations in postnatally diagnosed cases

Abstract: Over 600 cases with a Y aneuploidy (other than non-mosaic 47,XYY) were reviewed for phenotype/karyotype correlations. Except for 93 prenatally diagnosed cases of mosaicism 45,X/46,XY (79 cases), 45,X/47,XYY (8 cases), and 45,X/46,XY/47,XYY (6 cases), all other cases were ascertained postnatally. Special emphasis was placed on structural abnormalities. This review includes 11 cases of 46,XYp-; 90 cases of 46,XYq- (52 cases non-mosaic; 38 cases 45,X mosaic); 34 cases of 46,X,r(Y) (9 cases non-mosaic and 25 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
295
1
13

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(325 citation statements)
references
References 308 publications
(9 reference statements)
16
295
1
13
Order By: Relevance
“…Therefore, for patient B, the 45, X chimeric cells may have aggrevated his spermatogenic failure. In addition, a previous study has reported that once there is a 45, X cell line, regardless of whether there is Yp, Yq, or both Yp and Yq, or even a free Y chromosome in the other cells, there is an increased chance for that individual to be a phenotypic female [22]. In our mosaic case, the patient has a male phenotype.…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, for patient B, the 45, X chimeric cells may have aggrevated his spermatogenic failure. In addition, a previous study has reported that once there is a 45, X cell line, regardless of whether there is Yp, Yq, or both Yp and Yq, or even a free Y chromosome in the other cells, there is an increased chance for that individual to be a phenotypic female [22]. In our mosaic case, the patient has a male phenotype.…”
Section: Discussionsupporting
confidence: 47%
“…Two non-mosaic male patients were reported by DesGroseillier et al [2006] [8] who postulated that the isodicentric Y chromosome was stabilized early during gametogenesis in the father. The stability of dicentrics may result from inactivation of one of the centromeres [2], or due to presence of a very small distance between two active centromeres and thus behaving as monocentric [12]. To the best of our knowledge, there have been very few eports on formation of dicentric Y chromosome with breakage and fusion at the pseudo-autosomal regions.…”
Section: Case Reportmentioning
confidence: 99%
“…Among these structural abnormalities, dicentric Y chromosomes are the most commonly found [2,3]. These dicentric Y chromosomes correspond to two different types: dic (Yq), resulting from the fusion between the short arms of two Y chromosomes in which some Yp material is maintained, and dic (Yp) arising from fusion at the Yq arms.…”
Section: Introductionmentioning
confidence: 99%
“…Translocation of SRY to an autosome, most commonly to the short arm of an acrocentric (D or a G group) chromosome, has been reported in males lacking an obvious Y chromosome [5]. In the present case, the SRY gene was mapped to chromosome 13 by FISH analysis.…”
Section: Discussionmentioning
confidence: 67%